2018
DOI: 10.7717/peerj.5729
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of several commercially important river fish species from the Czech Republic

Abstract: Proximate and fatty acid (FA) composition of seven freshwater fish species from the Czech Republic were examined. Moreover, the index of atherogenicity (IA) and the index of thrombogenicity (IT) were calculated from the obtained data. These two indices along with the total content of the essential n-3 FAs, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) as well as the ratio of n-6/n3 FAs, provide good indicators for the nutritional value of the fish. The species had been selected owing to the limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 69 publications
2
14
1
1
Order By: Relevance
“…The results of the current research on AI and TI (Figure 6) are consistent with studies conducted by Linhartová et al [58] which found that the indicators in all analyzed fish, except for Nile tilapia, were below 0.5, which indicates significant benefit to human health if these fish are included in the human diet. AI and TI for seven freshwater fish species, including perch and bream, from the Czech Republic were close to the values given for the Eskimo diet, which indicates the high nutritional value of these fish and, therefore, not a threat [59]. According to Linhartová et al [58] the higher values of these coefficients, the higher risk of developing cardiovascular diseases, because AI indicates the risk of diseases such as atherosclerosis (deposition of fat in the walls of the arteries) and TI determines the possibility of blood clots.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The results of the current research on AI and TI (Figure 6) are consistent with studies conducted by Linhartová et al [58] which found that the indicators in all analyzed fish, except for Nile tilapia, were below 0.5, which indicates significant benefit to human health if these fish are included in the human diet. AI and TI for seven freshwater fish species, including perch and bream, from the Czech Republic were close to the values given for the Eskimo diet, which indicates the high nutritional value of these fish and, therefore, not a threat [59]. According to Linhartová et al [58] the higher values of these coefficients, the higher risk of developing cardiovascular diseases, because AI indicates the risk of diseases such as atherosclerosis (deposition of fat in the walls of the arteries) and TI determines the possibility of blood clots.…”
Section: Resultsmentioning
confidence: 56%
“…According to Linhartová et al [58] the higher values of these coefficients, the higher risk of developing cardiovascular diseases, because AI indicates the risk of diseases such as atherosclerosis (deposition of fat in the walls of the arteries) and TI determines the possibility of blood clots. Tilami et al [59] showed that AI and TI for bream and perch were 0.30 and 0.38 or 0.25 and 0.22, respectively. Similar values were found in these species of fish subject to this study (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Polak-Juszczak and Adamczyk [ 27 ] investigated freshwater fish from the Vistula Lagoon and reported protein contents similar to those found in the present study: bream (18.1 ± 0.5 g/100 g), eel 14.5 ± 0.8 g/100 g, perch (18.1 ± 0.5 g/100 g), pike-perch (19.5 ± 0.5 g/100 g), roach (18.3 ± 0.4 g/100 g). Khalili et al [ 28 ] also studied freshwater fish (lakes located in Czech Republic). All tested fish showed a level of protein like our study but it was lower than in Polish fish (17.1 ± 1.55 to 19.2 ± 2.20 g/100 g): bream (18.0 ± 1.24 g/100 g), perch (17.6 ± 1.85 g/100 g) and brown trout (19.2 ± 1.50 g/100 g).…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al [ 29 ] revealed that fat content of freshwater rainbow trout from fish farms in South Korea was 3.6 ± 0.2 g/100 g. Aggelousis and Lazos [ 38 ] demonstrated that fat content of freshwater fish from Greece ranged from 0.6 ± 0.21 to 3.5 ± 0.65 g/100 g and fat content of bream was 1.0 ± 0.48 g/100 g. Suloma et al [ 39 ] studied freshwater fish from Philippines and reported fat content from 2.54 ± 0.27 to 19.51 ± 1.78 g/100 g in each species. Badiani et al [ 28 ] reported mean fat content to be 7.63 ± 0.58 g/100 g. Bayse et al [ 32 ] showed that average fat content of freshwater fish was 6.2 ± 3.1 g/100 g. Bogard et al [ 34 ] revealed that fat content ranged from 0.30 to 18.3 g/100 g. Chandrashekar and Deosthale [ 33 ] demonstrated mean fat content of freshwater fish to be 1.0 ± 0.35 g/100 g. Fallah et al [ 30 ] showed that mean fat content was 5.01 ± 0.35 g/100 g in freshwater fish. Khalili et al [ 28 ] investigated freshwater fish from the Czech Republic and revealed that fat content ranged from 0.74 ± 0.04 g/100 g in perch to 4.04 ± 0.81 g/100 g in common nase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation